INTEGRATION OF ISLAM AND SCIENCE : THE STATE ISLAMIC UNIVERSITIES IN INDONESIA - Laminah; Abu Anwar (Jurnal Genta Mulia, 2024)
The integration of Islam and science at the State Islamic Universities (UIN) in Indonesia has been a topic of considerable interest and has undergone significant development. The transformation from the State Islamic Institutes (IAIN) into State Islamic Universities (UIN) in Indonesia aims to develop an ideal model for integrating science with Islam. This research employs a qualitative approach focusing on literature review. Hence, the study evaluates relevant literature materials and considers previous research studies on the integration of Islam and science. Data collection is carried out through exploring books, academic journals, and online platforms such as Google Scholar. Islamic Higher Education Institutions (PTKI) are higher education institutions with Islamic backgrounds. Since its establishment in 1957, PTKI has embraced an Islam-oriented approach by providing learning, skills training, and understanding of Islam. By the late 1990s, a new policy granted PTKI a broader mandate to open study programs and faculties related to general sciences. As a result, new faculties were formed, offering study programs in general science fields such as the Faculty of Economics and Business, Faculty of Psychology, Faculty of Social and Political Sciences, Faculty of Science and Informatics, and others.